2022
DOI: 10.1007/s11356-021-17965-7
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter–bound organic compounds: levels, mutagenicity, and health risks

Abstract: Increased industrialization and consumption of fossil fuels in the Metropolitan Region of São Paulo (MRSP), Brazil, have caused a growth of the particulate matter emissions to the atmosphere and an increase in population health problems.Particulate and gaseous phase samples were collected in different short campaigns (2015, 2016, and 2017) near an urban-industrial area. Organic carbon (OC), elemental carbon (EC), polycyclic aromatic hydrocarbons (PAH), and its derivatives (nitro and oxy-PAH), n-alkanes, hopane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…Any solid or liquid fuel combustion event generates airborne material that negatively affects air quality and health. This is due to the fact that volatile and unburnt products are inevitably generated by combustion processes that cannot in any way be ideal [ 1 , 2 ]. Such combustion events are the major sources of aerosols and exert significance influence on human health, air quality and global climate [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Any solid or liquid fuel combustion event generates airborne material that negatively affects air quality and health. This is due to the fact that volatile and unburnt products are inevitably generated by combustion processes that cannot in any way be ideal [ 1 , 2 ]. Such combustion events are the major sources of aerosols and exert significance influence on human health, air quality and global climate [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LECR ranged from 9.4 × 10 − 7 to 3.7 × 10 − 5 , which corresponds to an excess of approximately 0.1-3.7 lung cancer cases per 100,000 people. These estimated cancer risk values were similar to those calculated here based on the B[a]P concentrations reported in the Amazon region (0.2-5.0 lung cancer cases per 100,000 people; de Oliveira Alves et al, 2015), but were 1-2 orders of magnitude lower than those calculated from data reported for the megacity of São Paulo, where there are high vehicular and industrial inputs (6-200 lung cancer cases per 100,000 people; Caumo et al, 2022).…”
Section: Cancer Risk Assessmentsupporting
confidence: 86%
“…PM mass concentrations have shown a diminishing tendency in Europe due to more stringent regulations coupled with technological improvements (Daellenbach et al 2020 ), however, pollution from traffic, especially emission of diesel-powered vehicles, poses a serious environmental concern in Europe (Matthias et al 2020 ). Particles emitted by incomplete combustion carry a wide range of potentially toxic organic compounds including polycyclic aromatic hydrocarbons (PAHs) (Caumo et al 2022 ). Diesel engine exhaust was classified as carcinogenic to humans by the International Agency for Research on Cancer (IARC 2014 ).…”
mentioning
confidence: 99%